KEMUNGKINAN SUBTITUSI KAYU RAMIN (Gonystilus bancanus) DENGAN JENIS LAIN SEBAGAI PENGHARA PENGGERGAJIAN - Sukanda Sukanda; M Usmanyah (Jurnal Penelitian Hasil Hutan, 1991)
Forest harvesting on swampy  forests especially to  Ramin species in West Kalimantan has begun since 1958, consequently by now the forest potential of this species has decreased. The purpose of the  study is to evaluate a scoring system to tktel'mine the potential substitution of several wood speciesfor ramin which have similar ch,iracteristicsto Ramin in colour, textur, and other characterislia which .an considered importiint in wood utilization.                                                                                     .                                                          The result of this study showed that in West kalimantan it is estimated about 26 species have been used and have economic potential and in general dominated by family of diptecarpaceaein dry  land forest and Ramin in swampy forest. Using the scoring system, from 25 species of non Romin .it  wcu found  that there are 9 species which have simUarcharacteristicsto Ramin , namely, Cengal (Hope& sangal Korth.), Kayu Cina (Prodocarpus motlcyi  Dummer), Jelutung (Dyera  constulata   Hook.f},  Medang (Litsea  sp.), Meranliputih (Shorca  sp.), Mentibu (Dactylocladus stenoctachvs Oliv.), Perup•k (LOphopethallumpachylhyllum King), Pisang-pisang(Mezzettia parviv~oraBecc.) and Pulai (Alstonia scholaris'R.Br.).